Pengembangan Game Labirin Berbasis Artificial Intelligence Sebagai Media Pembelajaran Transformasi Geometri - Ferdiansyah Rigani; Nuraidah Zahra; Pebi Fauziyana Br Tarigan; Fevi Rahmawati Suwanto (Lembag, 2025)
This study aims to develop learning media in the form of an Artificial Intelligence-based maze game on geometric transformation material. The development of this learning media is motivated by the fact that mathematics learning tends to be boring, especially on geometric transformation material. This occurs because the application of monotonous learning methods, such as lecture methods, causes students to tend to be more passive and can lead to a decrease in student learning motivation. So the researcher developed a more interesting learning media in the form of an AI-based maze game to build student learning motivation. The game developed contains geometric transformation questions and presents them adaptively through AI logic. This research method uses an R&D (Research and Development) approach with the ADDIE model. The ADDIE stages are Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were ninth-grade students of SMP Yayasan Pendidikan Ghafa Medan. The results showed that this Artificial Intelligence-based maze game obtained a validity percentage of 82% with a very valid category, practicality obtained a percentage of 85.6% with a very practical category, and effectiveness obtained a percentage of 83.1% with a very effective category. The final evaluation showed that this learning tool was suitable for use, although improvements were still needed, such as adding penalties for wrong answers and enlarging the movement buttons. Overall, this AI-based maze game was deemed valid, effective, and practical as an interactive learning tool for geometric transformations.